Long-term follow-up in pediatric patients with paroxysmal hypothermia (Shapiro's syndrome). (November 2018) - Tambasco, Nicola; Paoletti, Federico Paolini; Prato, Giulia; Mancardi, Maria Margherita; Prontera, Paolo; Giordano, Lucio; Grosso, Salvatore; Romeo, Antonino; Pinto, Francesca; Savasta, Salvatore; Peruzzi, Cinzia; Romoli, Michele; et al.
Abstract: Introduction: Shapiro syndrome (SS) is characterized by spontaneous recurrent episodes of hypothermia, hyperhidrosis and corpus callosum (CC) agenesis. Less than 60 cases have been reported to date and the pathogenic mechanism as well as the prognosis of this syndrome are still debated. We describe the clinical features and long-term follow-up of a pediatric cohort of SS patients. Methods: We collected 13 (10 novel) pediatric cases of SS and report their long-term follow-up and neurological outcome. Results: All patients experienced recurring hypothermia, with body temperature below 35 °C during the episodes, often accompanied by hyperidrosis. CC agenesis was an inconstant structural feature in the present series (2/13 patients). Seven patients received antiepileptic drugs (AEDs) or other drug therapy for a mean period of 12 months. At long-term follow-up (mean = 61 months, range: 60–96), all individuals were free from episodes of paroxysmal hypothermia independently from previous AED use or other drug therapy. Conclusion: Paroxysmal hypothermia, the core symptom of SS, behaved as a age-dependent feature in our cohort, supporting a good long-term prognosis for SS. A prompt diagnosis of SS is crucial to avoid unnecessary diagnostic investigations. Highlights: Shapiro syndrome is characterized by spontaneous recurrent episodes of hypothermia. Shapiro syndrome in childhood appears to be self-limiting. Several cases of Shapiro syndrome without corpus callosum agenesis have been reported.